Financial Crisis and Global Governance : A Network Analysis - Sheng, Andrew (World Bank, Washington, DC, 2017)
This paper attempts to use network theory, drawn from recent work in sociology, engineering, and biological systems, to suggest that the current crisis should be viewed as a network crisis. The author surveys the concepts of networks, their defining characteristics, applications to financial markets, and the need for supervision and implications for national and global governance. Then, author briefly examines the current financial crisis in the light of the network analysis and surveys the recent reforms in financial regulation and architecture. The paper concludes with an analysis of the policy implications of network analysis.